Determinants of health seeking behaviour in South Sudan: a cross-sectional household survey - Ilja Obels; Harry Laurence Selby Coleman; Masja Straetemans; Margo van Gurp; George William Lutwama; Eelco Jacobs (BMC Public Health)
Abstract Background Access to healthcare is a major challenge in South Sudan, but evidence on the factors influencing health seeking behaviour (HSB) and the magnitude of their effect is limited. This study aims to identify which determinants are associated with seeking care for perceived health needs and with seeking care at private or public healthcare facilities in South Sudan. Methods A cross-sectional household survey was conducted in three purposefully-selected states (Central Equatoria, Western Equatoria and Warrap). A multi-stage, cluster sampling design was used. Univariable and multivariable logistic regression models were computed to explore the relationships between seeking care for perceived health needs and choice of facility, and individual and household characteristics based on an adapted Levesque framework. Results We identified that individuals who obtained medication (OR 2.45, 95% CI 1.15–5.23), obtained and paid for medication (OR 4.26, 95% CI 2.08–8.74), lived in Western-Equatoria (OR 9.05, 95% CI 2.35–34.54), and were aware of community health workers (CHWs) (OR 1.70, 95% CI 1.08–2.67), were significantly more likely to seek care for a perceived health need. Individuals who obtained and paid for medication (OR 3.03, 95% CI 1.59–5.81) and who lived further from a public health centre (OR 1.19, 95% CI 1.09–1.31) were more likely to seek care at a private facility, while individuals who had used the provider before (OR 0.52, 95% CI 0.34–0.78), lived in Western Equatoria (OR 0.24, 95% CI 0.13–0.46), lived in a rural household (OR 0.40, 95% CI 0.23–0.70) and had a longer travel time to the visited health facility, were less likely to seek care at a private facility. Conclusions Survey respondents’ state of residence and awareness of CHWs were associated with health seeking, while their state of residence, age, whether they paid for medication or not, travel time and distance to facilities were associated with choice of facility. Our results suggest differences in patterns of HSB between states, but studies with larger sample sizes are needed to analyse this. Furthermore, qualitative studies into access to healthcare in South Sudan could help characterise the nature of determinants and their relationship.